2016
DOI: 10.1515/nsad-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Problematic alcohol use and problem gambling: Associations to structural and functional aspects of social ties in a Finnish population sample

Abstract: AIMS-This study aims to explore associations between structural and functional aspects of social networks and relationships (here labelled social ties) among individuals exhibiting problematic alcohol use and problem gambling, respectively. MATERIAL & METHODS-Data was collected in the 2011 Western Finland Mental Health Survey, a postal questionnaire survey applying a stratified random sampling approach. The survey response rate was 46.2% (n = 4624, age range 15-80 years). Problem behaviours were assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In one Finnish population study (Castrén et al, 2013) loneliness was associated with problem gambling in regression analysis, interestingly however it was not associated with more severe gambling-related problems (such as gambling disorder). In another cross-sectional Finnish study looking at a population sample (Nordmyr et al, 2016), loneliness was associated with problem gambling. Sirola et al (2019) found that excessive gambling was higher among young Finns who reported higher levels of loneliness, with loneliness also positively moderating the association between excessive gambling and daily online gambling community participation in one of the included study samples.…”
Section: The Collected Evidence On Experienced Loneliness -Quantitatimentioning
confidence: 96%
See 1 more Smart Citation
“…In one Finnish population study (Castrén et al, 2013) loneliness was associated with problem gambling in regression analysis, interestingly however it was not associated with more severe gambling-related problems (such as gambling disorder). In another cross-sectional Finnish study looking at a population sample (Nordmyr et al, 2016), loneliness was associated with problem gambling. Sirola et al (2019) found that excessive gambling was higher among young Finns who reported higher levels of loneliness, with loneliness also positively moderating the association between excessive gambling and daily online gambling community participation in one of the included study samples.…”
Section: The Collected Evidence On Experienced Loneliness -Quantitatimentioning
confidence: 96%
“…In another study (Lyk-Jensen, 2010), respondents' retrospective views on their childhood and adolescence experiences related to feeling solitary and left out and feeling understood did not differentiate at-risk gamblers from no-risk gamblers (persons experiencing problem gambling were not included in the study). Further, one cross-sectional study (Nordmyr et al, 2016) of a Finnish population sample showed a positive association between low levels of neighbourhood trust and problem gambling, but no risk associated with general trust.…”
Section: Psychosocial Phenomena With a Limited Evidence Base In Nordimentioning
confidence: 97%
“…Loneliness in adult samples is associated with using alcohol and tobacco (Cacioppo et al, 2002;Greene et al, 2018;Shankur, McMunn, Banks, & Steptoe, 2011;Stanton, Moadel, Kim, Weinberger, & Shuter, 2015), greater use of sedatives and other psychotropic drugs (Boehlen et al, 2015;Taipale et al, 2011), and problematic drinking patterns (Bonin et al, 2000;Nordmyr, Forsman, & Österman, 2016;Stickley et al, 2013). Feeling lonely also appears to place people with many types of psychopathology at risk for substance misuse.…”
Section: Loneliness and Substance Usementioning
confidence: 99%
“…This finding is consistent with a recent research highlighting the association between cannabis, drunkenness episodes and problem gambling (Buja et al 2017), which suggests that female 'broad users' are a heterogeneous group which needs further research. Some potential common factors have been reported that account for a broad engagement in addictive behaviors such as higher levels of experienced loneliness (Nordmyr et al 2016) and poor emotional regulation (Estevez et al 2017). Further, differences in gambling severity may be explained by differences in the structural characteristics (e.g., event and bet frequency, event duration, inplay betting and payout interval) of the activities engaged in (Goodie 2015;Griffiths and Auer 2012).…”
Section: Journal Of Gambling Studiesmentioning
confidence: 99%